Disinformation and ‘Affect’ in the Cyberspace : The Case of Modi’s ‘New India' - Agrawal, Kshitij (2025)
The thesis ponders how democracies can stay intact in the digital age, problematizing disinformation today with the 'affective' dimensions of emotions. What emerges is a carefully constructed affective digital architecture, armed with reactionary publics & labelling of adversaries. The qualitative research on disinformation cases & search trends explore positive & negative 'affects' channelled or repressed in the Indian digital space to manufacture 'enemies' & 'others' to promote a populistic agenda. Such forces generate ignorance & affectivity to amplify populistic currents, curtail free expression & harm democracy in the long run.